A Phase 1 Study in Healthy Subjects to Evaluate the Safety and Pharmacokinetics of a Human Monoclonal Antibody (S315) Against Diphtheria Toxin - Sullivan-Bólyai, John Z; Allen, Larry B; Cannon, Rebecca; Cohane, Kenya P; Dunzo, Elise; Goldwater, Ronald; StCyr, Kathleen; Wang, Yang; Klempner, Mark S (The Journal of infectious diseases, 2024)
Diphtheria is a recurrent threat with endemic still occurs in many parts of the world. The standard of care is horse serum-derived diphtheria antitoxin (eDAT), which is in critical short supply globally. S315 is a fully human, monoclonal immunoglobulin G1 neutralizing antibody, specific to the receptor-binding domain of diphtheria toxin. S315 is intended to be a safer, more readily available alternative to replace eDAT. This first-in-human, randomized, double-blind, dose escalation study evaluated the safety, tolerability, and pharmacokinetics of S315 in healthy adults. Cohorts of study subjects received single intravenous infusions of S315 (480 mg, 960 mg, 1920 mg, 3840 mg, and 7680 mg) or matched placebo. Safety was assessed by standard clinical and laboratory evaluations. Serum S315 concentrations were measured by enzyme-linked immunosorbent assay (ELISA) and an in vitro diphtheria toxin neutralization assay, followed by pharmacokinetic analyses. Forty-one subjects were enrolled. S315 was safe and well tolerated. Most adverse events were mild or moderate. Peak mean serum concentrations ranged from 199 µg/mL to 2872 µg/mL (ELISA) and from 234 AU/mL to 1147 AU/mL (neutralization assay), with low variability. Mean serum half-life ranged from 12 to 27 days (ELISA) and from 17 to 22 days (neutralization assay). S315 was generally safe and well tolerated by healthy subjects. Pharmacokinetic data suggest that S315 serum neutralizing activity is an order of magnitude greater than that attained by eDAT. The results of this study support continued development of S315 as a replacement for eDAT to address critical global supply issues. Clinical Trials Registration. NCT04075175.